Nueva familia de angiospermas para el registro de la flora nativa de Chile: la familia Basellaceae - MOREIRA-MUÑOZ, ANDRÉS; MUÑOZ-SCHICK, MÉLICA (Gayana Botánica, 2018)
The presence of Anredera diffusa, from the Basellaceae family, is reported for the first time for the Chilean flora. This species was found in the locality of Mancaruma, north of Socoroma town, in the Arica y Parinacota Region. This is the first record of a native species of Basellaceae in Chile.